2013
DOI: 10.5797/jnet.7.24
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of idiopathic cervical internal carotid artery vasospasms with carotid artery stenting: a report of 2 cases

Abstract: Objective Case 1 Case 2 ConclusionKey Words

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…On attacks, stellate ganglion block, 8) arterial papaverine hydrochloride injection, 1) and steroid therapy 1,6) have been used. For prevention, calcium antagonists, 1,3,4,6-8,10,11) antiplatelet durgs, [1][2][3]7) anticonvulsive drugs, 8) and oral steroids 1) have been selected. Several studies reported the efficacy of these treatments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On attacks, stellate ganglion block, 8) arterial papaverine hydrochloride injection, 1) and steroid therapy 1,6) have been used. For prevention, calcium antagonists, 1,3,4,6-8,10,11) antiplatelet durgs, [1][2][3]7) anticonvulsive drugs, 8) and oral steroids 1) have been selected. Several studies reported the efficacy of these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, these drug therapies did not completely reduce vasospastic attacks in some patients. [1][2][3][4] Some studies indicated the efficacy of CAS 3,4) although the number of patients was small. In the present case, drug-resistant attacks had repeatedly occurred 5 to 6 times a month for 10 years or more, and cerebral infarction developed during the course, leading to a severe condition; therefore, bilateral CAS was performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations